(untitled) (Revista de Crítica Literaria Latinoamericana, 2012)
Chicana poetry found a place in American cultural studies and literature during the 60s. Since then, Chicana/o authors have obtained an uncontestable position in the canon of American literature. They have not enjoyed this privilege in Mexican and Latín American poetry, where they are relatively unknown. This article examines the poetry of Américo Paredes, Alberto Urista -Alurista-, Ana Castillo, Lorna Dee Cervantes, and Tino Villanueva, to underscore their contributions to Mexican and Latin American literatures. Their multilingual work occupies an interstitial space between Spanish, English, Spanglish, Engliñol, while looking for greater visibility among Hispano- and Latin American readers and critics. The notion of "Mechicana Poetics" places the work of Chicana/o and Latina/o poets in the US within indeterminate space of nepantla or inbetween-ness. This space ruptures limits and pre-established maps. It suggests the creation of a border without borders, where the quality of the writing and the transnational imaginary of the poets establish their distinction.